Reading Luke-Acts in its Mediterranean milieu - Talbert, Charles H. 1934-2021 (Leiden [u.a.] Brill, 2003)
This volume pulls together thirteen essays written by the author since the late 1970's which give a distinctive, coherent reading of Luke-Acts. Twelve of the essays focus on the theological perspectives of Luke and Acts as they can be discerned from the angle of vision of the "authorial audience" as delineated by the non-biblical literary critic, Peter J. Rabinowitz. The final essay focuses on the possible historical value of Acts and the methodology involved in judging that possibility.
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Archivierung prüfen
Keywords: Bible -- N.T -- Luke -- Criticism, interpretation, etc; Bible -- N.T -- Acts -- Criticism, interpretation, etc; Bible -- Criticism, interpretation, etc; Bible -- Criticism, interpretation, etc; Bibel; Bibel